2019
DOI: 10.1111/nyas.14237
|View full text |Cite
|
Sign up to set email alerts
|

Genomic analysis of a multidrug‐resistant clinical Providencia rettgeri (PR002) strain with the novel integron ln1483 and an A/C plasmid replicon

Abstract: Whole‐genome sequence analysis was performed on a multidrug‐resistant Providencia rettgeri PR002 clinical strain isolated from the urine of a hospitalized patient in Pretoria, South Africa, in 2013. The resistome, mobilome, pathogenicity island(s), as well as virulence and heavy‐metal resistance genes of the isolate, were characterized using whole‐genome sequencing and bioinformatic analysis. PR002 had a genome assembly size of 4,832,624 bp with a GC content of 40.7%, an A/C2 plasmid replicase gene, four integ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 53 publications
(106 reference statements)
4
42
0
Order By: Relevance
“…Integron 191 was however identified in four different STs suggesting a diversity of clones with this MGE. The dominance of the class 1 integron in this study is also consistent with genomes found in Africa, Europe and South America 8,31,41,44 . Two novel integrons identified had the aadA16 cassette variant in K021 as well as dfr30b and dfrA14b cassette variants in K145, confirming the ongoing evolutionary processes in these genomes resulting in the diversity of gene cassettes in K. pneumoniae.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Integron 191 was however identified in four different STs suggesting a diversity of clones with this MGE. The dominance of the class 1 integron in this study is also consistent with genomes found in Africa, Europe and South America 8,31,41,44 . Two novel integrons identified had the aadA16 cassette variant in K021 as well as dfr30b and dfrA14b cassette variants in K145, confirming the ongoing evolutionary processes in these genomes resulting in the diversity of gene cassettes in K. pneumoniae.…”
Section: Discussionsupporting
confidence: 90%
“…The presence of the bla CTX-M , bla TEM , bla OXA , and bla SHV ESBL genes in similar genetic contexts have been described previously in same and different species in South African and international isolates 7,8,12,19,20,[31][32][33][34][35][36] . The presence of these ARGs within the same genetic context and on the same plasmid replicons across same and different species around the globe strongly suggests the clonal and plasmid-mediated spread of these ARGs.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…These species have been implicated in fatal infections such as sepsis and wound infections 31,34,39,62,63 , bearing critical ARGs such as ESBLs and carbapenemases ( Fig. S11, S20, S24-S25).…”
Section: Discussionmentioning
confidence: 99%
“…Resistance to ciprofloxacin was mediated by GyrA [S83I] chromosomal mutation, plasmid-mediated quinolone resistance genes (PMQR) (aac(6')-Ib-cr and qnrB1), and efflux genes ( [15] reported that high-level fluroquinolone resistance was mediated by efflux, PMQR genes, and gyrA mutations in Enterobacterales, including Citrobacter freundii, which supported our results. More so, efflux genes belonging to three main efflux pump systems ( Table 2) reported to play vital roles in antibiotic resistance in Enterobacterales were also identified [18,19]. However, the mere presence of these efflux genes does not directly implicate resistance, and hence further studies on their expression levels will be needed to ascertain the possibility of efflux pump hyperexpression [18].…”
Section: Discussionmentioning
confidence: 99%